Castleman disease (literature review) - A. L. Melikyan; E. K. Egorova (Онкогематология)
Castleman disease (angiofollicular hyperplasia of lymph nodes) – a rare benign lymphoproliferative disease with prolonged asymptomatic course, associated with a wide variety of autoimmune and oncological diseases and the risk of non-Hodgkin’s lymphoma. The rare occurrence of this disease and a variety of clinical course did not allow for a complete and consistent research on the etiology and pathogenesis and the standard therapies development. In recent years, the number of patients with Castleman disease in the Russian Federation has increased, which requires its recognition among non-neoplastic and neoplastic lymphadenopathy. The article provides an overview about clinical and histological variants of Castleman’s disease, its pathogenesis concepts, classification and treatment.